Characterization of regenerative agricultural practices and drivers of their adoption in mixed farming systems - Mulupi, Dennis Kimoso; Mose, Phoebe Bwari; Wasike, Chrilukovian Bwire (International Journal of Sustainable Agricultural Research, 2025)
Despite regional efforts to promote regenerative agriculture (RA), its contribution to the global food market has remained insignificant. This low market contribution has been attributed to the low adoption of regenerative agricultural practices (RAPs). Increasing the adoption of RAPs is crucial for sustainable agricultural production, maintaining production resources, and reducing production costs, ultimately increasing market share. Therefore, this study aimed to characterize RAPs in mixed farms and examine the factors driving their adoption. The study was conducted in Trans-Nzoia and Uasin Gishu counties, Kenya. A cross-sectional questionnaire survey was conducted to collect primary data from 397 farms using a multi-stage sampling approach. Data on RAPs, their distribution, challenges, and drivers of adoption were collected. The findings revealed that fodder production, managed grazing, the use of crop residue as feed, diversification of animal and plant species, and legume production had high adoption rates. Intercropping, retaining crop residue, crop rotation, and agroforestry practices had moderate adoption rates. Composting, mulching, zero-tillage, organic farming, water harvesting, irrigation, terracing, ridge construction, and integrated pest management had low adoption. Additionally, 39.55%, 59.95%, and 0.50% of the farms had low, moderate, and high adoption of RAPs, respectively. The binary logistic regression model showed that adoption was positively influenced by farmer training, farmers’ attitudes, benefit level, land ownership status, crop type, and subsidy programs. The study established that adoption of RAPs was low. Therefore, improved farmer training, targeted subsidy programs, and streamlined processing of land title deeds are recommended to accelerate adoption.